2011
DOI: 10.1111/j.1747-4469.2011.01258.x
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Rewards of Elite Status in the Legal Profession

Abstract: This article focuses on the role of intergenerational status attainment for legal careers. By decomposing the earnings gap between elite and nonelite lawyers at two points in their careers, we find that inherited cultural capital produces an earnings advantage as soon as lawyers begin their careers and that this gap persists over time. We further find that the processes underlying this gap change as lawyers make their way through the profession. While in early careers, the elite advantage is due to stronger st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…We measure the effect of social background by entering a binary variable for father's education (with fathers with graduate or professional schooling compared to all others). An extensive body of research identifies father's education as a measure of parental status (Dinovitzer 2011;Hauser and Warren 1997;DiMaggio and Mohr 1985). Father's education has been found to be strongly correlated with mother's education and to have fewer missing or difficult-to-interpret cases (Jaeger and Holm 2003).…”
Section: Social Backgroundmentioning
confidence: 99%
“…We measure the effect of social background by entering a binary variable for father's education (with fathers with graduate or professional schooling compared to all others). An extensive body of research identifies father's education as a measure of parental status (Dinovitzer 2011;Hauser and Warren 1997;DiMaggio and Mohr 1985). Father's education has been found to be strongly correlated with mother's education and to have fewer missing or difficult-to-interpret cases (Jaeger and Holm 2003).…”
Section: Social Backgroundmentioning
confidence: 99%
“…Other scholars have highlighted the impact of law school prestige on attorneys’ career prospects (Dinovitzer, ). Kay and Hagan (:498–99) conclude that “[t]he contacts that elite law school students make through their schooling play a significant role in shaping their career path.” To account for the influence that law school experiences may play on later professional experiences and career satisfaction, we follow the approach of prior studies by including categories based on the U.S. News and World Report 's law school rankings (Dinovitzer and Garth, ; Dinovitzer, ; Sander and Bambauer, ). These are broken down into six categories, which track the law school rankings, with our excluded category being those considered “fourth tier” (ranked above 150).…”
Section: Methodsmentioning
confidence: 99%
“…Along these lines, network analyses show that white males occupy different employment networks than women and minorities, and these networks are not equal in prestige or their ability to translate into successful employment outcomes (Dinovitzer, ; Kim, ). Because trust helps to smooth the way for social exchanges, traits such as race and gender can stand in for trustworthiness in the absence of information (McDonald, :320), which can impact the effectiveness of an attorney not from the majority demographic group.…”
Section: Bias and Stereotyping In The Legal Professionmentioning
confidence: 99%
“…Third, research examining the legal profession has identified several demographic factors as important determinants of labor market success, including gender (Dinovitzer 2011;Dinovitzer et al 2009;Hagan 1990;Hull and Nelson 2000), race (Dinovitzer et al 2009;Hull and Nelson 2000;Wilkins et al 2007), and age (Dinovitzer et al 2009;Wilkins et al 2007). Measures for each of these factors are included in the analyses.…”
Section: Dependent Measurementioning
confidence: 99%
“…An important point that nearly all new lawyers will face in their careers is the transition from law school into the legal labor market. Indeed, it is during this time that the foundations of their future careers are laid as they come to occupy career trajectories that will prove consequential for years to come (DiPrete and Eirich 2006; see also Dinovitzer 2011;Hagan 1990;Hull and Nelson 2000;Kay and Hagan 1998;Rivera 2011). As such, this period has received considerable attention in the literature as a predictor of future occupational success.…”
Section: Introductionmentioning
confidence: 99%